A systematic review of fishing impacts on the trophic level of fish populations and assemblages in the Mediterranean Sea - Marguin, Audrey; Bussotti, Simona; Guidetti, Paolo; Rossi, Francesca (Frontiers in Marine Science, 2025)
Fishing activities alter food web diversity and functioning. Trophic level (TL) has been used as an indicator to assess such impacts on populations and assemblages. We reviewed the scientific literature that examined the relationship between fishing and the trophic aspects of fish species and communities, by focussing on TL. We narrowed the research to the Mediterranean Sea, where fishing is an important economic income for some coastal human populations and might be jeopardised by overfishing and climate change. We collected information on the (i) geographical location; (ii) type of fisheries and (iii) the methodological approach. The 68 collected studies were geographically skewed towards the Western Mediterranean, Adriatic Sea and around Greece. Among the 45 modelling studies, 41 reported TLs for communities or catches. For the field studies, only 6 estimated TLs of species and used stable isotope analysis. Most modelling studies used data from other models, online databases or large-scale monitoring of commercial catches and research surveys, whereas the field studies collected fish locally. Only 6 field and 5 modelling studies used fishing bans or the fully protected zone of marine protected areas as no-fishing control. In these studies, TL values showed different patterns of response to fishing, probably because of differences in environmental factors. Interestingly, recent modelling studies used predictions from the model to explore the impact of different fishing pressure within global change scenarios. The use of trophodynamic modelling is powerful to describe large scale impacts and infer future scenarios, but the in situ approach, the use of stable isotopes and spatial comparisons among areas of different fishing pressure, such as no-take zones in MPA could add insights into local variations of fish TLs in response to perturbations, which might be important to refine the outcomes of the models.